Nonlinear Trade-Off Between Agitator Speed and Biodiesel Quality in Transesterification: A Lab-Scale Study - Prasetiyo, Dani Hari Tunggal; Danang, Danang Yudistiro; Robertus, Robertus Sidartawan; Iqbal, Iqbal Ramadhani; Asroful Abidin, Asroful Abidin (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2026)
The agitator speed controls the intensity of interaction between the immiscible oil and methanol phases during transesterification. This, in turn, shapes the overall reaction environment during the biodiesel production process. While higher agitation rates are often associated with increased mass transfer, their impact on the resulting fuel properties is not always proportional. In a controlled laboratory setting, the effect of agitator speed was examined at 300, 500, 700, and 900 rpm, with particular attention paid to biodiesel yield, density, kinematic viscosity, and flash point. A gradual shift in system behavior became apparent as the agitation rate increased. In the intermediate range of 500–700 rpm, the process tended to stabilize, producing biodiesel with relatively consistent characteristics. The measured kinematic viscosity was between 4.42 and 4.45 cSt, accompanied by a density of approximately 861 kg/m³. However, pushing the system to higher agitation rates led to a different response. At 900 rpm, the yield dropped sharply to 49.53%, and the viscosity increased to 4.92 cSt. This behavior indicates the onset of unfavorable hydrodynamic conditions, where intensive mixing likely disrupts phase separation and promotes the formation of a stable emulsion. Meanwhile, the flash point continued to increase from 124.7 °C to 166.8 °C, indicating a progressive decrease in residual methanol. Overall, these observations suggest that the influence of stirrer speed is governed by competing mechanisms rather than a simple monotonic trend. Operation in the 500–700 rpm range appears to offer a more reliable compromise, where conversion and fuel properties remain balanced. From an engineering perspective, this range provides a useful reference for establishing operating conditions in biodiesel reactors, especially when considering process development beyond the laboratory scale while maintaining consistent product quality.